Analysis of 20 genes at chromosome band 12q13: RACGAP1 and MCRS1 overexpression in nonsmall‐cell lung cancer. Issue 3 (8th December 2012) - Liang, Yurong; Liu, Minxia; Wang, Pin; Ding, Xiaojie; Cao, Yi
Abstract Chromosomal aberrations at 12q13 are frequent in nonsmall‐cell lung cancer (NSCLC). Here, we examined mRNA expression of 20 genes within chromosome band 12q13 by quantitative real‐time polymerase chain reaction in NSCLC. Of the 20 genes, nine were upregulated, while two genes were downregulated. Among the nine upregulated genes, mRNA values of RACGAP1, MCRS1, EIF4B, WNT1, and PTGES3 were significantly higher in NSCLCs compared with normal lung tissues. Subsequently, overexpressions of RACGAP1 and MCRS1 were confirmed at the protein level in tissues and cultured cells of lung cancer by immunostaining and Western blot. RACGAP1 was labeled in the nucleus of tumor cells in 89% of the tumor specimens. In the cultured cells, RACGAP1 was present principally in the nucleus of nonmitotic cells, but showed a diffuse distribution in the cytoplasm of mitotic cells (metaphase) and at the contractile ring between two separating daughter cells (telophase). Furthermore, RACGAP1 downregulation by RNA interference caused cytokinesis defects, indicating that RACGAP1 is required for cytokinesis. MCRS1 was stained in all tumor specimens and strongly stained in 31% of cases. Interestingly, MCRS1 exhibits different localization in the mitotic cells of cultured immortalized human bronchial epithelial cells and cultured lung cancer cells. In vitro, downregulation of MCRS1 in lung cancer cells inhibited cell proliferation, increased apoptosis, and induced cell cycle arrest at the G1 phase. These findings indicate that RACGAP1 and MCRS1 may be cancer‐related genes in NSCLC. © 2012 Wiley Periodicals, Inc.